Relationship between Character and Socio-psychological Adaptation of Personality to Higher Education - Terletska, Larysa; Chistyakova, Anastasia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article presents the results of an empirical study of the relationship between character and socio-psychological adaptation of the individual to university education. Concepts analyzed: character, adaptation, socio-psychological adaptation to learning, adolescence. Diagnostic research methods were used (Oldham-Morris questionnaire to determine personality types and Rogers-Diamond research methods to determine socio-psychological adaptation of personality); methods of mathematical statistics. In the field of psychological and pedagogical research, the problem of adaptation of students is one of the priorities, as it is located at the junction of different fields of knowledge that are crucial in the modern conditions of higher education. The purpose of the study: to identify the relationship between personality types and socio-psychological adaptation in students. The conducted empirical research allows to draw the following conclusions: in general, the subjects had a high level of adaptation, self-acceptance, acceptance of others, emotional comfort, internality, which indicates good social adaptability; the average level of desire for domination, which allows them to have self-esteem, not to be constantly subordinate to others, but also does not lead to authoritarianism, dictatorship. Among the personality types of the most popular is the "Honest" type, also common are "Dramatic" and "Active".
Keywords: character; adaptation; socio-psychological adaptation to learning; adolescence